'Gorilla exceptions' and the ethically apathetic corporate lawyer. Issue 1 (2nd January 2016) - Vaughan, Steven; Oakley, Emma
ABSTRACT: This paper draws on interviews with 57 corporate finance lawyers working from global law firms based in the City of London. Drawing on this data, we highlight common themes of taking deals at 'face value', being the lawyer-technician who uses the law to effect his client's wishes, and not 'pushing' ethics. We suggest that there is an apathy – a lack of concern or interest – about ethics on the part of corporate lawyers. This apathy stems from various sources. It is linked to assumptions about the sorts of clients that large law firms are willing or not willing to act for, and assumptions about the 'right sort of people' the firm hires and retains; it is linked to strong notions of role morality; and it is founded on the classic legal ethics 'standard conception' principles of neutrality and non-accountability. Our data also highlights a lack of ethical infrastructures in large firms, and a lack of ethical leadership from law firm partners for the associates and trainees working for them.